Application of The Self-Learning Arena Model to Improve Understanding of Norm Recognition Material in Everyday Life - Neneng Kaniawati; Sunarso Sunarso (PT Publikasiku Academic Solution, 2025)
At this time, human life is entering a new era: the era of digital industrialization. As a result, various human needs have become increasingly reliant on internet support and the digital world as a vehicle for interaction and transactions. This study aims to analyze the application of the Arena Belajar Mandiri (ABM) learning model in improving students' comprehension skills of the Introduction to Norms in Daily Life material at SMA Negeri 1 Purwadadi. The research method employed a qualitative research approach, specifically a type of classroom action research (PTK). The research subjects consisted of 36 students from class X-3. Data collection techniques using tests and observations. The data analysis technique involved comparing the class average value of the test results from each cycle with classical completeness using a predetermined formula. The results showed that students' understanding of the material of the introduction of norms in everyday life could increase after applying the ABM learning model in cycle I and cycle II. This is indicated by an increase in classical completeness from 22.22% in the initial data to 52.78% in cycle I, and then to 80.56% in cycle II. Thus, this research concludes that the application of the Arena Belajar Mandiri (ABM) model can improve students' comprehension skills.